El coro de los maestros carniceros - Erdrich, Louise (Nuevos tiempos (Madrid, Spain), 2012)
Returning to his quiet German village home after World War I, trained killer Fidelis Waldvogel, accompanied by his wife, leaves to start a new life in America and finds his life irrevocably changed by a new relationship.